2004
DOI: 10.1111/j.1365-2699.2004.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Quaking aspen (Populus tremuloides Michx.) at treeline: a century of change in the San Juan Mountains, Colorado, USA

Abstract: During a repeat photography study quaking aspen (Populus tremuloides Michx.) was observed invading conifer stands at treeline in the San Juan Mountains of south‐western Colorado. Aspen tree core samples were collected from nine plots ranging in elevation from 3192 to 3547 m, and estimated dates of establishment of aspen were grouped into 10‐year intervals for analysis. Estimated periods of establishment were compared with century‐long climate data records to derive any correlations with aspen invasion. Other d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 46 publications
6
53
1
2
Order By: Relevance
“…The San Juan Mountains experience a summer rainy season that usually begins in July due to an influx of monsoonal air from the Gulf of Mexico and the Gulf of California (Keen, 1996). Previous studies suggested a mean annual temperature of 3.2°C and an average annual precipitation of 428 mm at high-elevation weather stations (2,660-2,710 m), although this varies considerably across elevation (Elliot and Baker, 2004). Aspen forests are found from around 2,350 to 3,250 m elevation in this region, co-occurring with ponderosa pine (Pinus ponderosa) forests at the lower end and Engelmann spruce (Picea engelmannii)/subalpine fir (Abies lasiocarpa) forests at the upper end (Worrall et al, 2008).…”
Section: Field Sitesmentioning
confidence: 99%
“…The San Juan Mountains experience a summer rainy season that usually begins in July due to an influx of monsoonal air from the Gulf of Mexico and the Gulf of California (Keen, 1996). Previous studies suggested a mean annual temperature of 3.2°C and an average annual precipitation of 428 mm at high-elevation weather stations (2,660-2,710 m), although this varies considerably across elevation (Elliot and Baker, 2004). Aspen forests are found from around 2,350 to 3,250 m elevation in this region, co-occurring with ponderosa pine (Pinus ponderosa) forests at the lower end and Engelmann spruce (Picea engelmannii)/subalpine fir (Abies lasiocarpa) forests at the upper end (Worrall et al, 2008).…”
Section: Field Sitesmentioning
confidence: 99%
“…(hereafter aspen) stands are an important forest type in the intermountain region of the United States [1]. Recently, increased study of aspen stand dynamics, particularly "sudden aspen decline" [2] has led to a large body of literature suggesting aspen loss is due partly to a reduction of stand-replacing disturbances as the result of grazing, 20th century fire suppression, an extremely moist 20th century, and subsequent succession [3][4][5]. It is assumed that fire was an integral driving process in historic aspen stand dynamics [6]; however, the role of fire likely varies between seral and stable aspen stands.…”
Section: Introductionmentioning
confidence: 99%
“…For example, climate change and fire suppression may have influenced aspen stand regeneration (Romme and others, 1995;Elliott and Baker, 2004). The presence of rapidly growing Estes Park, located within the winter range, has provided forage (highly productive, fertilized lawns, golf courses, and ornamental shrubs) for an increased wintering population of elk in town since the late 1970s (R.J. Monello, T.L.…”
Section: Introductionmentioning
confidence: 99%